2018
DOI: 10.1088/1361-6528/aac6b0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trapped charges and hysteresis behavior in hBN encapsulated single MoS2 flake based field effect transistors on SiO2 and hBN substrates

Abstract: Molybdenum disulfide (MoS) based field effect transistors (FETs) are of considerable interest in electronic and opto-electronic applications but often have large hysteresis and threshold voltage instabilities. In this study, by using advanced transfer techniques, hexagonal boron nitride (hBN) encapsulated FETs based on a single, homogeneous and atomic-thin MoS flake are fabricated on hBN and SiO substrates. This allows for a better and a precise comparison between the charge traps at the semiconductor-dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…5). The most widely observed issues in 2D devices are the hysteresis of the gate transfer characteristics 11,12,45,54,58 and long-term drifts of the threshold voltage [90][91][92] , which are commonly known from Si technologies as BTI, given their strong bias and temperature dependence 85 . Recent analysis of experimental results for MoS 2 58,70,71,93,94 and black phosphorus 23,50 using non-radiative multiphonon (NMP) models 95 (see more details in Box 2) suggests that hysteresis and BTI have the same microscopic origin and result from changes in the charge state of border traps (Fig.…”
Section: Box 2 | Details On Non-radiative Multiphonon Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…5). The most widely observed issues in 2D devices are the hysteresis of the gate transfer characteristics 11,12,45,54,58 and long-term drifts of the threshold voltage [90][91][92] , which are commonly known from Si technologies as BTI, given their strong bias and temperature dependence 85 . Recent analysis of experimental results for MoS 2 58,70,71,93,94 and black phosphorus 23,50 using non-radiative multiphonon (NMP) models 95 (see more details in Box 2) suggests that hysteresis and BTI have the same microscopic origin and result from changes in the charge state of border traps (Fig.…”
Section: Box 2 | Details On Non-radiative Multiphonon Modelsmentioning
confidence: 99%
“…The most widely studied crystalline insulator for 2D materials is hBN 11,45,54,58 . Devices using hBN typically exhibit a sizable improvement in terms of SS 54 and mobility 11 and also show considerably reduced charge trapping compared to 3D oxides 45,58 . This can be explained by the well-defined surface of hBN and the low density of border traps in this crystalline material.…”
Section: Future Development Of 2d Electronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both methods confirmed that the composite film based on phthalocyanine nanowire and P3HT in the same weight ratio can offer the best hole transfer capability, which is the fundament of high short‐circuit current density ( J SC ) and fill factor (FF) . We also calculated the trap density (N T ) of HTM thin films based on the change in threshold voltage (ΔV T ), obtained by the hysteresis curves of thin films in FET devices and using the formula N T = −ΔV T C ox /q . As shown in Figure , the largest ΔV T between two curves was observed for phthalocyanine nanowire thin film.…”
Section: Summary Of Photovoltaic Parameters Of Pscs Employing N‐cume2mentioning
confidence: 99%